THE EFFECTIVENESS OF USING PROBLEM BASED LEARNING MODEL IN NABAWIAH PARENTING MATERIAL ON CHARACTER OF STUDENTS OF BUANA PERJUANGAN UNIVERSITY KARAWANG - Masruroh, Siti; Rahmatiani, Lusiana; Christine, Debbie (International Journal of Psychosocial Rehabilitation, 2020)
This research is backed by the condition of the lower social sensitivity and the student courtesy because of the rapid influence of information technology. The problem that is researched is the effectiveness of the use of Model Problem Based learning on the material Parenting Nabawiah against the character. The purpose of this research is to determine the effectiveness of the use of Problem Based learning models. The population taken is an entire class in the course of Information Systems Force 2018 Semester 1. Sampling techniques with purpose sampling variable dependent the caller is the use of a model of problem Based Learning and Variebel Free is the result of student learning. The data collection techniques used in this study were tests and used test N. Gain. as a data analysis technique to determine the improvement of learning outcomes, based on the results of the research on the experimental class on Ngain test which is 0.55 which means that in medium category and in the control class there is a result of 0.29 which is in low category Experimental classes are superior due to the use of more interactive learning models that facilitate students in absorbing learning. The problem based learning model is an interactive learning model, digging the knowledge of students for having the problem and solving it together